Development and evaluation of hearing conservation program among vector control workers / Rama Krishna Supramanian - Rama Krishna, Supramanian (2020)
Noise-induced hearing loss (NIHL) is one of the highest recorded occupational disease despite being preventable. In 2018, occupational noise-induced hearing loss was the highest reported occupational disease experienced by workers in Malaysia accounting for 87.7% of all occupational diseases. The aim of this study is to develop, implement and evaluate the effectiveness of a Hearing Conservation Program (HCP) in preventing noiseinduced hearing loss among vector control workers. This study is divided into two phases: development of HCP (phase 1) and implementation and evaluation of HCP (phase 2). The development phase (phase 1) included a review, interview with key stakeholders and reviewing local and international guidelines. In phase 2, the HCP was implemented and evaluated using a cluster-randomized controlled trial design. A total of 183 vector control workers from nine district health offices in the state of Perak, Malaysia were randomized to intervention or control group. The multifactorial intervention included noise exposure monitoring, noise control, proper use of hearing protection devices, training and education session, audiometric testing and hazard communication. Three strategies for NIHL prevention were identified from the review: championed by leaders, one-off training and multifactorial intervention (combination of multiple strategies). The mean age of the participants were 37.7 and 36.6 years old in the intervention and control group respectively. The majority of participants in both groups were males, Malay ethnicity, and general workers with a highest education level of secondary education. The baseline mean hearing threshold observed for the grouped frequencies (2, 3 and 4 kHz) was higher among the intervention group (24.9 dB) compared to the control group (16.1 dB) for the left ear. Similar trends were observed for the right ear with 23.6 dB (intervention) and iii 14.8 dB (control). As for the grouped frequencies (0.5, 1, 2 and 3 kHz) the intervention group also showed higher mean hearing threshold compared to the control group with 20.8 dB (left ear) and 22.1 dB (right ear). The baseline mean score for knowledge, attitude and practice score towards NIHL was 77.8, 75.1 and 62.9 for intervention group while the control group participants averaged 73.5, 70.7 and 71.2. After 3 months, the intervention group showed a greater reduction (0.06 dB reduction) in mean hearing threshold in the left ear for the grouped frequencies (2, 3 and 4 kHz). As for the grouped frequencies (0.5, 1, 2 and 3 kHz) both intervention and control group showed a reduction in mean hearing threshold of 1.4 dB and 2.6 dB respectively for the left ear. There was also a greater improvement in the mean score for knowledge, attitude and practice towards noise-induced hearing loss (NIHL) in the intervention group as compared to the control group but were not statistically significant. The HCP has shown to be effective in preserving hearing of vector control workers as well as improving their knowledge, attitude and practice towards NIHL. Trial registration: TCTR20190109002 Funding: University of Malaya Grand Challenge (PEACE) (GC001A-14HTM) Keywords: noise-induced hearing loss, vector control worker, occupational exposure